Pragmatic Theory in Education: The Case of Iran (London Journal of Research In Humanities and Social Sciences, 2024)
The application of pragmatic theories, particularly Dewey's views, in pedagogy has brought about significant transformations in educational systems worldwide. However, in the case of Iran, the implementation of pragmatist theories in education has faced various challenges. This paper examines the Iranian educational system, focusing on the obstacles  hindering the application of pragmatist theories for children aged 8-12. It explores the characteristics of pragmatist theories and analyzes three dimensions of the Iranian educational structure: (1) defining childhood, child marriage, and child labor; (2) the socialbackgrounds of education in Iran; and (3) the educational facilities necessary for effective pedagogy. The conclusions highlight political factors and the absence of a robust educational model as the main barriers to realizing pragmatist pedagogy for Iranian children aged 8-12.
Keywords: teaching practices; school volleyball; verbal intervention; didactic regulation; acceptance and inclusion of refugee students; acceptance and respect for otherness; cooperation; empathy and emotional intelligence; experiential learning; open school; reduction in intra-school violence; strengthening of family ties.; Convergence; social capital; NREGA/MGNREGA/MGNREGS; BPL and APL Household; diversity; Vietnam.; folk woodcut art; modern woodcut art; 21st-century; creative work; Challenges; Pragmatic theory; Pedagogy; Educational systems